Practicum design for making bioplastics from uli banana peel (Musa paradisiaca S.) to grow the character of the pancasila student profile in polymer chapter - Alfandi Ahmad; Retno Aliyatul Fikroh (Pascasarjana Universitas Negeri Medan, 2023)
The change from the 2013 curriculum to the Merdeka curriculum emphasizes the importance of experiential learning and the Pancasila student profile. However, polymers, a crucial macromolecular sub-material, often lack experimental support in education. This study focuses on selecting polymer materials through practical activities, specifically the creation of bioplastics from uli banana peels (Musa paradisiaca S), to foster the development of Pancasila Student Profile characteristics: collaborative teamwork, critical thinking, and innovation. Using a qualitative descriptive method, the study involves curriculum analysis, practical design, and feasibility assessment. The research revealed that the practical design aligns with the characteristics of high school experiments and produces high-quality bioplastics in terms of absorbency, tensile strength, elongation percentage, and biodegradability. Teacher and student interviews further confirmed the alignment with the Pancasila phase F student profile (class XII), emphasizing cooperation, objective-oriented learning, critical thinking, and innovation. This study establishes a strong connection between curriculum, learning outcomes, and experimental design in uli banana peel starch bioplastics production. Not only does it promote the development of Pancasila student profiles, but it also yields high-quality bioplastics.Keywords: Bioplastic; Merdeka curriculum; Pancasila; Polymer; Uli banana